5-year outcomes of transcatheter aortic valve replacement compared with standard treatment for patients with inoperable aortic stenosis (PARTNER 1): a randomised controlled trial. Issue 9986 (20th June 2015) - Kapadia, Samir R; Leon, Martin B; Makkar, Raj R; Tuzcu, E Murat; Svensson, Lars G; Kodali, Susheel; Webb, John G; Mack, Michael J; Douglas, Pamela S; Thourani, Vinod H; Babaliaros, Vasilis C; Herrmann, Howard C; et al.
Summary: Background: Based on the early results of the Placement of Aortic Transcatheter Valves (PARTNER) trial, transcatheter aortic valve replacement (TAVR) is an accepted treatment for patients with severe aortic stenosis who are not suitable for surgery. However, little information is available about the late clinical outcomes in such patients. Methods: We did this randomised controlled trial at 21 experienced valve centres in Canada, Germany, and the USA. We enrolled patients with severe symptomatic inoperable aortic stenosis and randomly assigned (1:1) them to transfemoral TAVR or to standard treatment, which often included balloon aortic valvuloplasty. Patients and their treating physicians were not masked to treatment allocation. The randomisation was done centrally, and sites learned of the assignment only after a patient had been screened, consented, and entered into the database. The primary outcome of the trial was all-cause mortality at 1 year in the intention-to-treat population, here we present the prespecified findings after 5 years. This study is registered with ClinicalTrials.gov, number NCT00530894 . Findings: We screened 3015 patients, of whom 358 were enrolled (mean age 83 years, Society of Thoracic Surgeons Predicted Risk of Mortality 11·7%, 54% female). 179 were assigned to TAVR treatment and 179 were assigned to standard treatment. 20 patients crossed over from the standard treatment group and ten withdrew from study, leaving only six patients at 5 years, of whom five had aortic valve replacement treatment outside of the study. The risk of all-cause mortality at 5 years was 71·8% in the TAVR group versus 93·6% in the standard treatment group (hazard ratio 0·50, 95% CI 0·39–0·65; p<0·0001). At 5 years, 42 (86%) of 49 survivors in the TAVR group had New York Heart Association class 1 or 2 symptoms compared with three (60%) of five in the standard treatment group. Echocardiography after TAVR showed durable haemodynamic benefit (aortic valve area 1·52 cm 2 at 5 years, mean gradient 10·6 mm Hg at 5 years), with no evidence of structural valve deterioration. Interpretation: TAVR is more beneficial than standard treatment for treatment of inoperable aortic stenosis. TAVR should be strongly considered for patients who are not surgical candidates for aortic valve replacement to improve their survival and functional status. Appropriate selection of patients will help to maximise the benefit of TAVR and reduce mortality from severe comorbidities. Funding: Edwards Lifesciences.